EVALUATION OF THE UTILIZATION OF REAL-TIME MELTING CURVE ANALYSES ON A 3D-POLYACRYLAMIDE DNA MICROCHIP FOR THE GENOTYPING OF SINGLE NUCLEOTIDE POLYMORPHISMS IN THE MDR1 GENE - PHOON YEE PENG (2011)
Master's